Evaluation of Mathematics History Learning: Improving Students' Journal Writing and Presentation Skills for Publication - Vivekanantharasa Raveenthiran; Hafizatunnisa Hafizatunnisa (Rangkiang Mathematics Journal, 2026)
The History of Mathematics Learning course is often taught theoretically and descriptively, thus not fully encouraging students to develop applicable academic skills, particularly in scientific writing and publication. In fact, scientific journal publication is an important indicator in strengthening students' academic literacy. This study aims to evaluate the effectiveness of a project-based learning program for scientific journal writing and presentation in improving students' academic competencies. The method used is a qualitative approach with a program evaluation design based on the CIPP (Context, Input, Process, and Product) model. The study subjects comprised 57 students in the Mathematics Education Study Program who were taking the History of Mathematics Learning course. The instruments used consisted of interview guidelines, observation sheets, and documentation of student articles. Data analysis was conducted qualitatively through thematic analysis and document analysis techniques. The results show that this program is relevant to students' academic needs, supported by good resource readiness, and implemented systematically through a cycle of presentations and revisions that build a scientific culture. The scientific articles produced by students showed a significant quality improvement, with the majority successfully submitted to SINTA-indexed national journals. These findings suggest that integrating scientific journal writing into mathematics history courses not only enhances students’ critical thinking and academic literacy but also helps prepare future educators for scholarly publication, highlighting broader implications for mathematics education.